Beaches - Marshall, Garry; Donoghue, Mary Agnes; Midler, Bette; Hershey, Barbara, 1948-; Heard, John, 1946-; Gray, Spalding, 1941-2004.; Read, James, 1952-; Kazan, Lainie; Dart, Iris Rainer; Touchstone Pictures; Silver Screen Partners IV.; Touchstone Home Video (Firm); et al. (Burbank, Calif. : Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 2002)
Two childhood friends are reunited in their middle age and one learns she is dying of a fatal disease.
Originally produced as a motion picture in 1988.
Based on the novel by Iris Rainer Dart.
Special features: bloopers; music video: 'Wind Beneath My Wings' by Bette Midler; "AFI's 100 years ... 100 songs with Bette Midler"; Mayim Bialik remembers Beaches; Barbara Hershey screen test; audio commentary; theatrical trailer.
Director of photography, Dante Spinotti ; film editor, Richard Halsey ; music, Georges Delerue.
Bette Midler, Barbara Hershey, John Heard, Spalding Gray, James Read, Lainie Kazan.
MPAA rating: PG-13.
Keywords: Female friendship -- Drama; Terminally ill -- Drama; French language materials; Feature films